The role of geographical factors in the genocide of the population of Halabja district - Karim, Asst.Prof.DrAhmad Rafiq Karim; Osman, Khabat Nooruddin Osman (Sulaimani Journal for Humanities, 2025)
The use of chemical weapons is considered one of the gravest crimes committed by the Ba’ath Party regime against the residents of Halabja. This catastrophe left a profound and long-lasting economic, social, historical, and civilizational impact on both the geographical environment and its inhabitants. The significance of this research lies in determining the role of natural and human factors in the region, as well as examining the influence of geography and military operations in Halabja on the extent of losses in human lives, property, and the environment. The study aims to uncover the underlying factors responsible for the extermination of Halabja’s population. Given the nature of the inquiry, a historical, descriptive, and analytical approach was adopted. Geographic Information System (GIS) was employed to develop the maps used in the research. Data and information were sourced from the following agencies: the meteorological departments of Sulaymaniyah and Halabja, the Halabja Memorial Monument, the Agency of Martyrs and Anfal Affairs, the Department of Statistics in Sulaymaniyah, and the General Hospital of Halabja. In addition, field interviews were conducted with several relevant stakeholders. The findings revealed that the chemical attack on the city of Halabja by the former Iraqi regime was not merely a transient military operation; rather, it was a systematic attempt at the genocide of a specific ethnic group. Being a predominantly Kurdish area, Halabja was targeted by the Ba’ath Party regime, under the leadership of Saddam Hussein, through its violent practices aimed at erasing the Kurdish national identity and undermining its political struggle and existence. Furthermore, the chemical assault on Halabja was executed according to a premeditated military plan by the former regime because they knew where the crowded areas of the city, such as basements and underground shelters, are located during the attacks. Consequently, toxic gases capable of infiltrating low-lying areas and enclosed environments were deliberately employed. The attack also capitalized on the meteorological conditions outside the city, particularly the wind direction and speed, by specifically utilizing gases heavier than air that can disperse and flow toward lower areas. The overall structure of the study is divided into three main axes: the first axis addresses the influential natural geographical factors; the second focuses on human geographical factors; and the third examines the political and military geographical factors in the study area.
Keywords: Geographical Factors; Genocide; Population; Halabja; Political Geography